ANALISA DEFECT KAYU PADA PROSES WOODWORKING DI PT. BERDIKARI MEUBEL NUSANTARA - Putri, Digitha Oktaviani; Subagja, Ahmad; Rofieq, Mochammad; Kautsar, Fuad (LENVARI, 2025)
At PT. Berdikari furniture Nusantara which is a manufacturing company that produces furniture. In the implementation of the production process has 11 stages of the process and the woodworking process into a process with the most reject data of 15.2% for the reject process in each process. In the woodworking process found damaged wood (broken, chunk, damaged) as much as 22% which became the most common type of defect found in the woodworking process. From the existing data, the use of FTA (fault tree analysis) method aims to analyze the factors that cause defects in products. FMEA (failure mode & effect analysis) method aims to identify and determine the proportion and priority of factors causing product defects that must be repaired immediately. From these methods obtained the results of the analysis for the FTA is that there are 4 basic root causes of 2 causal factors, namely the absence of job desc and responsibility, no understanding of maintaining product quality, no work instructions, and no habit of continuous improvement. The results of FMEA analysis that has been conducted interviews at the head of the quality control department that has not understood about maintaining the quality is meant by having a value of RPN (risk priority number) of 252. Available for 3 employees who actually have RPN values each are not yet familiar with ongoing habits with a value of 175, not to mention work instructions with a value of 144, and the most rare are job desc and responsibilities with a value of 48. In the end, the root cause of the improvement will be discussed again so that it is hoped that it can have a positive effect on the company.